PENGARUH INFORMASI PRODUK PADA FITUR LIVE STREAMING SHOPEE TERHADAP PURCHASE INTENTION DAN HABIT - Sephia Ramadanti; Osa Omar Sharif (Universitas Bina Taruna Gorontalo, 2023)
This study aims to analyze the effect of the live streaming feature on the Shopee application on purchase intention through product uncertainty as a mediator at Shopee in Bandung City. Primary data was obtained from the results of a questionnaire of 400 Shopee consumers in the city of Bandung. With purposive sampling method and data analysis using SPSS and SmartPLS software. The results showed that Real-time Communication and Perceived Authenticity had a significant negative effect on Product Quality Uncertainty in the purchasing process on Live Streaming Shopee. As well as Perceived Authenticity has a significant negative effect on Product Fit Uncertainty in the purchase process on Live Streaming Shopee. Perceived Enjoyment, and Convenience Of Product Search have a significant positive effect on Habit in the buying process on Live Streaming Shopee. And finally, Product Quality Uncertainty and Habit are stated to have a significant effect on Purchase Intention in the purchase process on Live Streaming Shopee. In addition, perceived enjoyment has a very significant effect on habit and convenience of product search also has a very significant effect on habit.